Relief Tiles from Halich: The European Context - Matveev, Vasilii N. (Actual Problems of Theory and History of Art, 2017)
Ceramic tiles of different types and sizes were widely used in the decoration of the churches of Old Rus. They were covered with yellow, green, and brown glaze, sometimes they were also decorated with ornament. Only in Halich region, in some churches, there were tiles with reliefs where figures and ornamental images were depicted. The complete absence of similar samples in other regions of Old Rus gave a reason for some scholars to look for analogical tiles in neighboring countries and to derive them from Byzantine or Romanesque art. To understand how such unusual elements of decoration appeared in Halich, it is necessary to place them in the context of European decorative ceramics of that time. In general, decorative ceramic tiles were widely spread in the medieval architecture of Europe and NearEast; but in different regions, there were some peculiar types. In Constantinople, there were actively used tiles of white clay covered with bright painted glaze ornaments with prevalence of yellow, green, and brown colors. In the Seljuk Sultanate of Konia, at the end of the 12th century, there were tiles made of white clay as well, covered with white and blue glaze ornament, often they were of cruciform or of star shape. In France and German, the tiles began to be actively used at the end of the 12th century, in Britain — in the middle of the 13th century. There they were made of red clay, at first covered with monochrome glaze; the method of pouring red clay in a white clay form in order to achieve a bicolor effect appeared in the middle of the 13th century. Only in Polish and Czech lands the tiles with reliefs of floral motifs and story images were widely spread. So, it becomes clear that the only places where the relief tiles were found were the countries of Central Europe,where they were actively used from the end of the 12th century. That is why it seems natural that such plates appeared in Halich lands, which were in cultural interaction with these countries. In spite of the fact that the method of placement of an image in a circle was widespread in Europe, as well as the depiction of gryphons,peacocks, and other creatures on tiles, the relief tiles are typical for certain geographical and cultural zone of theCentral European countries. Finally, if we take into consideration the peculiarities of political history of Halich Russia in the middle of the 13th century, the active contacts of Daniil of Galicia with his western neighbors and the presence of similar by technique and shape tiles in Lesser Poland, it seems logical that this region was the origin of the tiles of that type.